FRUSTRATION THEORIES - Usmonova Nargiza Raximjonovna (Modern American Journals, 2025)
This article explains in detail about frustration, theories of frustration, S. Rosensweig's theory of frustration, J. Dollor's theory of frustration aggression, K. Lewin's field theory and Z. Freud's psychoanalytic theory.
Keywords: Frustration, aggression, defense mechanisms, needs, field theory, theory of aggression, depression, apathy.